Sequence diversity in the Dickeya fliC gene: phylogeny of the Dickeya genus and TaqMan® PCR for 'D. solani', new biovar 3 variant on potato in Europe. - Johan Van Vaerenbergh (Public Library of Science (PLoS), 2012)
Worldwide, Dickeya (formerly Erwinia chrysanthemi) is causing soft rot diseases on a large diversity of crops and ornamental plants. Strains affecting potato are mainly found in D. dadantii, D. dianthicola and D. zeae, which appear to have a marked geographical distribution. Furthermore, a few Dickeya isolates from potato are attributed to D. chrysanthemi and D. dieffenbachiae. In Europe, isolates of Erwinia chrysanthemi biovar 1 and biovar 7 from potato are now classified in D. dianthicola. However, in the past few years, a new Dickeya biovar 3 variant, tentatively named 'Dickeya solani', has emerged as a common major threat, in particular in seed potatoes. Sequences of a fliC gene fragment were used to generate a phylogeny of Dickeya reference strains from culture collections and with this reference backbone, to classify pectinolytic isolates, i.e. Dickeya spp. from potato and ornamental plants. The reference strains of the currently recognized Dickeya species and 'D. solani' were unambiguously delineated in the fliC phylogram. D. dadantii, D. dianthicola and 'D. solani' displayed unbranched clades, while D. chrysanthemi, D. zeae and D. dieffenbachiae branched into subclades and lineages. Moreover, Dickeya isolates from diagnostic samples, in particular biovar 3 isolates from greenhouse ornamentals, formed several new lineages. Most of these isolates were positioned between the clade of 'D. solani' and D. dadantii as transition variants. New lineages also appeared in D. dieffenbachiae and in D. zeae. The strains and isolates of D. dianthicola and 'D. solani' were differentiated by a fliC sequence useful for barcode identification. A fliC TaqMan®real-time PCR was developed for 'D. solani' and the assay was provisionally evaluated in direct analysis of diagnostic potato samples. This molecular tool can support the efforts to control this particular phytopathogen in seed potato certification.